2020
DOI: 10.3389/fcell.2020.579137
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin as an Important Driver of Genome Organization

Abstract: Heterochromatin is a constituent of eukaryotic genomes with functions spanning from gene expression silencing to constraining DNA replication and repair. Inside the nucleus, heterochromatin segregates spatially from euchromatin and is localized preferentially toward the nuclear periphery and surrounding the nucleolus. Despite being an abundant nuclear compartment, little is known about how heterochromatin regulates and participates in the mechanisms driving genome organization. Here, we review pioneer and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 99 publications
2
46
0
Order By: Relevance
“…The involvement of heterochromatin in genome functioning, adaptation, and speciation is still a fundamental problem of modern genetics. The notion that CH is a genetically inactive part of the genome has been refuted [ 1 , 45 , 46 , 47 , 48 , 49 , 50 ]. The position effect on gene expression depends on the proximity to the site of CH and apparently may reflect intranuclear location of genes at interphase [ 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of heterochromatin in genome functioning, adaptation, and speciation is still a fundamental problem of modern genetics. The notion that CH is a genetically inactive part of the genome has been refuted [ 1 , 45 , 46 , 47 , 48 , 49 , 50 ]. The position effect on gene expression depends on the proximity to the site of CH and apparently may reflect intranuclear location of genes at interphase [ 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Partitioning of euchromatin and heterochromatin is an important layer of chromatin organization. Whereas euchromatin comprises transcriptionally active regions of the genome, heterochromatin corresponds to condensed forms of chromatin with poor, or no, transcriptional activity [ 284 ]. Heterochromatin is categorized into two major types: constitutive and facultative.…”
Section: Molecular Mechanisms Whereby Sumoylation Can Regulate Polmentioning
confidence: 99%
“…This prompted us to investigate chromatin and RNA Polymerase 2 (Pol2) status in PGCs using immunohistochemistry. First, we analyzed H3K9 tri-methylation (H3K9me3) as a mark associated with heterochromatin and repressed transcription ( Penagos-Puig and Furlan-Magaril, 2020 ). Using the signal from the somatic cells to normalize, we found that H3K9me3 in PGCs dropped between 1 dpf and 6 dpf ( …”
Section: Resultsmentioning
confidence: 99%